Imagens do Empreendedorismo: Uso de Metáforas para a Pesquisa sobre o Fenômeno Empreendedor (Management and Connections Journal, 2022)
In this paper, we present a non-systematic literature review on metaphors applied to the study and research of entrepreneurship. In order to do so, we prioritize papers that developed entrepreneurship metaphors and applied them to the understanding of entrepreneurship theoretical approaches. In this paper, we explored three entrepreneurial metaphors: entrepreneurship as a process; entrepreneurship as a practice; and entrepreneurship as a network. Furthermore, we discussed some implications of these metaphorical approaches to entrepreneurship research. Thus, the reflexive, critical feature that each metaphor assume may contribute to the understanding of entrepreneurial actions related to entities such as the entrepreneur, the business, and the context, in one hand, and to theoretical constructs such as processes, practices, and networks, on the other hand, thus leading the way to the metaphorical constitution of “images of entrepreneurship”.
Keywords: Entrepreneurship; Process; Practice; Networks; Metaphor